Reliability analysis of geotechnical infrastructures : introduction - Zhang, Wengang (2019)
In the design of geotechnical infrastructure, engineers have to deal with naturally occurring soils and rocks which are subjected to spatial variability as well as other uncertainties such as errors in measurement and in modeling methods. Reliability assessment which provides a systematic approach for quantifying the risk of failure has been shown to be a promising tool for solving these challenging geotechnical engineering problems. The method provides a more consistent measure of the level of safety or “structural reliability” through the evaluation of a reliability index and the associated “failure” probability, and is a method that satisfies the need to clearly convey safety issues to the public and regulatory authorities. Various methods for calculating the reliability of geotechnical infrastructures with regard to the assessment of the ultimate and serviceability limit states have been proposed by many researchers and these approaches include: the direct Monte Carlo Simulation, Bayesian and other sampling techniques, the first-order reliability method and the second-order reliability method, the random field method, the response surface method and other surrogate models with the related probabilistic procedures.